2016
DOI: 10.1891/1945-8959.15.2.163
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Classroom Composition Research on Social-Emotional Outcomes: Introduction to the Special Issue

Abstract: Classroom composition research on social-emotional outcomes (CCRSO) aims to systematically explore how characteristics of classmates are related to the social-emotional outcomes of children and adolescents. In this introduction to the special issue, we first provide an overview of the scientific roots of CCRSO. We then develop a conceptualization of research areas typically of interest in CCRSO, which comprises 4 different fields of inquiry. Based on this, an overview on exemplary studies in these areas of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 120 publications
(142 reference statements)
0
28
0
5
Order By: Relevance
“…The studies mentioned above, however, so far ignored the question whether, beyond individual characteristics, classroom characteristics (e.g., sociocultural composition, cognitive ability of peers) might also affect student outcomes in inclusive educational settings. As known from school effectiveness research, aggregate-level characteristics might moderate the effects of student-level characteristics on individual outcomes (e.g., Müller & Zurbriggen, 2016). Overall, most of these studies (e.g., Hattie, 2002;Van Ewijk & Sleegers, 2010) showed that characteristics of the composition of the learning environment can increase the effect of disadvantaging individual characteristics on outcomes.…”
Section: Empirical Evidence On Effects Of Inclusive Education On Achimentioning
confidence: 99%
“…The studies mentioned above, however, so far ignored the question whether, beyond individual characteristics, classroom characteristics (e.g., sociocultural composition, cognitive ability of peers) might also affect student outcomes in inclusive educational settings. As known from school effectiveness research, aggregate-level characteristics might moderate the effects of student-level characteristics on individual outcomes (e.g., Müller & Zurbriggen, 2016). Overall, most of these studies (e.g., Hattie, 2002;Van Ewijk & Sleegers, 2010) showed that characteristics of the composition of the learning environment can increase the effect of disadvantaging individual characteristics on outcomes.…”
Section: Empirical Evidence On Effects Of Inclusive Education On Achimentioning
confidence: 99%
“…Social dynamics are relational, negotiated, and often fluid (Adler & Adler, 1998; Cairns & Cairns, 1994). They also depend on the characteristics of the individuals who make up the social system as well as proximal and broader societal rules and expectations that govern their social opportunities (Farmer, Reinke, & Brooks, 2014; Müller & Zurbriggen, 2016).…”
Section: Meaning Of Social Dynamicsmentioning
confidence: 99%
“…Social dynamics depend on the composition of the classroom including size, student characteristics, familiarity of students with each other, and amount of time students are together (Farmer, 2000; Müller & Zurbriggen, 2016). Also, social structures will vary from classroom to classroom in terms of how students sort themselves into groups, density of social connections, characteristics of peer leaders, degree to which a social hierarchy is formed, and general social norms.…”
Section: Considerations For Multitiered Systems Of Support and Intervmentioning
confidence: 99%